Patulous nasolacrimal duct with air reflux: a complication of submucosal diathermy of the inferior turbinate - Puttasiddaiah, P M; Whittet, C R; Shuttleworth, G N (Journal of laryngology and otology, 2018)
Submucosal diathermy to the inferior turbinate is a widely practised procedure to improve the nasal airway when nasal obstruction is due to hypertrophy of the inferior turbinate. This paper reports a case of an unusual nasolacrimal complication following submucosal diathermy to the inferior turbinate, and reviews the relevant literature.Case reportA 33-year-old male patient developed a patulous nasolacrimal duct opening following submucosal diathermy of the inferior turbinate. This resulted in spontaneous reflux of air and nasal mucus on to the ocular surface. This newly recognised complication of submucosal diathermy to the inferior turbinate indicates the need to be aware of the potential risk to the nasolacrimal system with this technique.